Damage detection in compressed natural gas (CNG) cylinders based on auxiliary mass induced frequency shift - Zhang, Yao (2015)
This paper proposes a new damage detection method for cylindrical shell structures based on the frequency shift induced by an auxiliary mass. The natural frequency of a cylindrical shell changes when an auxiliary mass is placed at different positions on its surface. In fact, when the auxiliary mass is approaching the damage resulting in a decrease of local stiffness, the natural frequencies will drop drastically. This is because the auxiliary mass increases the local mass. That is, the auxiliary mass can enhance the influence of the damage on the dynamic characteristics of the cylindrical shell, and therefore, it can be used to probe the damage by traversing it over the entire surface of the cylindrical shell. On the other hand, the sudden drop of natural frequencies induced by the auxiliary mass approaching the damage can be considered as an anomaly since the frequencies usually change smoothly under the assumption that intact cylindrical shell is homogeneous and smooth. To detect the anomaly, a new damage index is proposed based on the curvature of frequency shift, which only uses the information from the damaged cylindrical shell. The proposed method is then tested on a damaged CNG cylinder; it demonstrates that it is more accurate and sensitive compared to other traditional vibration based damage detection methods which depend on mode shape instead.